Permasalahan Kronologis Prasasti Pupus - Wibowo, Aditya Krisna; Rahayu, Andriyanti (Paradigma: Jurnal Kajian Budaya, 2020)
The Pupus inscription, which was made of metal, has suffered from a lot of corrosion, especially in the area where the date was inscribed, which has cast doubt on its actual chronology. When we are dealing with an ancient inscription, such lack of chronological clarity can cause historical uncertainty. The purpose of this study was to ascertain the chronology of the Pupus inscription. This study used the comparative method. The data in this study consisted of the Pupus inscriptions as primary data and other inscriptions from two specific eras: i.e. the Kadiri period and Kayuwangi-Balitung period, as secondary or comparative data. The results show that the Pupus inscription was issued during the Dyah Balitung period, i.e. in 822 Śaka, but was copied in the 10th century A.D. or during the Kadiri era.